Grit, discounting, & time inconsistency - König-Kersting, Christian; Trautmann, Stefan T. (Working papers in economics and statistics, 2023)
We study the association of the perseverance-of-effort (PoE) and the consistency-of-interests (CoI) components of the psychological measure of grit, with economic measures of impatience and decreasing impatience (time inconsistency), respectively, in the general population. We find that impatience is associated with grit through the PoE component. No association of time inconsistency with grit is found. Predicting participants' financial and health outcomes and behaviors, we find that both impatience and grit are predictive for both outcomes, but this is not the case for time inconsistency. Our findings suggest that it can be beneficial for empirical studies of intertemporal decisions to include both economic impatience and psychological grit measures.
Keywords: Graue Literatur